The Influence of Using Animated Video Media on Students' Motivation and Understanding in Science Learning in Grade V of SD Negreri 29 Kota Pagar Alam - Hopsah, Siti Nur Umi; Dhori, Muhammad; Maria, Lira; Jelita, Yusika Purnama; Pratiwi, Ajeng Julia (JURNAL PENDIDIKAN DASAR NUSANTARA, 2025)
This study aims to determine the effect of using learning videos on the motivation and understanding of science concepts of elementary school students. The study was conducted using the Classroom Action Research (CAR) model in two cycles at SD Negeri 29 Kota Pagaralam, involving 30 fifth grade students. The results showed an increase in learning motivation and understanding of concepts after using learning videos. In cycle I, most students did not understand the material well, but in cycle II there was a significant increase in both student participation and learning outcomes. Learning videos have been proven to be able to create a more interesting learning atmosphere and help students understand abstract science material.